Bio-products from Serratia marcescens isolated from Ghanaian Anopheles gambiae reduce Plasmodium falciparum burden in vector mosquitoes - Akorli, Esinam Abla; Ubiaru, Prince Chigozirim; Pradhan, Sabyasachi; Akorli, Jewelna; Ranford-Cartwright, Lisa (Frontiers in Tropical Diseases, 2022)
Novel ideas for control of mosquito-borne disease include the use of bacterial symbionts to reduce transmission. Bacteria belonging to the family Enterobacteriaceae isolated from mosquito midgut have shown promise in limiting Plasmodium intensity in the Anopheles vector. However, the mechanism of interaction between bacteria and parasite remains unclear. This study aimed at screening bio-products of two bacteria candidates for their anti-Plasmodial effects on mosquito stages of P. falciparum. Enterobacter cloacae and Serratia marcescens were isolated from field-caught Anopheles gambiae s.l. Spent media from liquid cultures of these bacteria were filtered, lyophilized and dissolved in sterile phosphate buffered saline (PBS). The re-dissolved bacterial products were added to gametocytaemic blood meals and fed to An. gambiae mosquitoes via membrane feeders. Control groups were fed on infected blood with or without lyophilized LB medium. The effect of the products on the infection prevalence and intensity of P. falciparum in mosquitoes was assessed by dissecting mosquito midguts and counting oocysts 10-11 days post-infection. S. marcescens bio-products elicited significant reduction in the number of mosquitoes infected (P=4.02 x10-5) with P. falciparum and the oocyst intensity (P<2 x 10-16) than E. cloacae products (P>0.05 for both prevalence and intensity) compared to the control (lyophilized LB medium). These data support the use of bioproducts released by S. marcescens for malaria control based on transmission blocking in the vector.